Piled Modifiers, Buried Verbs, and Other Turgid Prose in the American Political Science Review. Issue 1 (18th January 2022) - DeScioli, Peter; Pinker, Steven
ABSTRACT: Academic writing is notoriously difficult to read. Can political science do better? To assess the state of prose in political science, we examined a recent issue of the American Political Science Review. We evaluated the articles according to the basic principles of style endorsed by writing experts. We find that the writing suffers most from heavy noun phrases in forms such as noun noun noun and adjective adjective noun noun. Further, we describe five contributors that swell noun phrases: piled modifiers, needless words, nebulous nouns, missing prepositions, and buried verbs. We document more than a thousand examples and demonstrate how to revise each one with principles of style. We also draw on research in cognitive science to explain why these constructions confuse, mislead, and distract readers.